UPAYA PELESTARIAN SENI MADIHIN MELALUI PEMBELAJARAN PUISI - Abdul Salam (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2019)
This study aims to find out and describe the development of poetry reading materials to meet the need of madihin art preservation in accordance with the demands of the curriculum and local cultural wisdom. The study used descriptive qualitative method. The data was collected through observation and interview techniques. The results are then processed by extracting and providing data, interpreting and presenting data, and analyzing data. The study was conducted in odd semester 2018/2019 with research subject the students of class X of SMKN 3 Banjarbaru. The results of the study concluded, the development of poetry teaching materials through madihin speech is very relevant to the purpose of poetry learning, while at the same time increasing students awareness to preserve traditional madihin arts.